State Aid Causing Distinct Incentives? Quasi-Experimental Measurement of the Effects of Grants on Private Enterprises in North Macedonia. (April 2022) - Petreski, Marjan
The objective of this study is to measure the effects of state aid distributed to private enterprises in North Macedonia on the enterprises' efficiency. We examine the governmental Plan for Economic Growth (PEG) pursued through the Financial Support of Investment Law (FSIL) and the Fund for Innovation and Technological Development (FITD). We rely on a rigorous impact evaluation method, whereby comparison groups are sourced from the pool of rejected applicants for the two programs. We pursue conditional matching on firms' observables and then apply the difference-in-differences method to isolate the effect of the subsidy. FSIL State Aid showed largely ineffective, with producing hardly any difference in sales, investment, wages, or profits among recipients, except employment. These results demonstrate the absence of the incentive effect as it relates to FSIL state aid. On the other hand, the FITD State Aid showed to be considerably effective, as the recipients were found to have increased their sales revenue and their investment in technology and profits, corroborating the presence of the incentive effect as it relates to FITD state aid. Notwithstanding the legitimacy of the policy objective to equalize domestic and foreign firms in terms of their access to state aid, these findings document partial failure of the PEG to do so due to its structural problems. JEL classification : H25, C90